Gambaran Kadar Asam Urat pada Lansia - Rizki Kurniawan; Kartinah Kartinah (Journal of Telenursing (JOTING), 2023)
This study aims to describe uric acid levels in older people in Pucangan Village, Kartusara District. The method used in this research is a quantitative method using a descriptive approach. The results obtained from this study were an examination of uric acid levels showing that normal uric acid levels had the highest frequency of 60.4%. In comparison, high uric acid levels were as much as 39.6%. In conclusion, older people in the Posyandu of Pucangan Village gender dominated this study, namely women; the majority of the ages from the study's results were the age range of 60-65 years, and the most educational level status was elementary school. With the results, uric acid levels are still expected, and women most experience high uric acid levels. Keywords: Uric Acid, Elderly